Harvesting Waste Heat Energy from Automobile Engine Exhaust Using Teg with Heat Pipes - Balakrishnan, Arun Seeralan; Nagi, Farrukh; Salleh, Khairul; Gunnasegaran, Prem A L (International Journal of Engineering and Technology, 2018)
This research investigates how the heat from car exhaust pipe line can be recovered as power using passive Thermo electric generator(TEG) using heat pipes. In this research the heat pipes are place on the cold side of TEG to remove the rising temperature and hot side of TEG is placed on the circumference of exhaust pipe line of car engine. The heat pipes with and without nano-fluids were placed on cold side of TEGs to investigate heat removal from increasing temperature and too maintain constant temperature on cold side. On the basis of results from 3D finite element simulations and experiments in the setup, the heat flow, voltage, and current were measured. The method presented in this paper gives detailed insight into how TEG modules perform in general, and also enables prediction of potential improvement in module performance by using different nano-fluids as coolants and Preliminary results were obtained. The results of Finite Element Analysis are analogous with the experimental results of TEG with water filled heat pipes with minimal possible errors. Therefore, the performance of nano-fluids in heat pipes are numerically evaluated and proposal are made for the enhancement of Module power outputs in Harnessing exhaust heat energy.
Keywords: Thermo electric generator; heat pipes; waste heat energy; Nano fluids exhaust heat energy and green house effects